UPAYA MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS 9B MATERI ADVERTISEMENT TEXT MENGGUNAKAN MEDIA BOARD GAME DENGAN METODE BLENDED LEARNING - Endarwati, Endarwati (Jurnal Analisis Pendidikan Sosial, 2024)
This research aims to find out the increasing activeness of students learning in online learning through the media board games in English subjects. This study is a class action study with the research subjects of grade IX students MTs N 2 Mojokerto as many as 30 people. This research was conducted 2 cycles, each cycle consisting of 2 meetings. At each meeting consists of 4 stages namely planning, implementation, observation and reflection. Data collection techniques used include interviews and observations. Based on the results of the study, in cycle I obtained an average student learning activity of 65.63% with enough categories. while in cycle II, the average learning activity of students is 79.69% with a high category. Thus, from cycle I and cycle II there was a 14.06% increase in student activity. thus it can be concluded that through the board games can increase the active learning of grade IX students of MTs N 2 Mojokerto towards English speaking skills, especially advertisement text materials in online learning during the covid-19 pandemic.